2016
DOI: 10.1002/2015jc011365
|View full text |Cite
|
Sign up to set email alerts
|

Propagation of uncertainty and sensitivity analysis in an integral oil‐gas plume model

Abstract: Polynomial Chaos expansions are used to analyze uncertainties in an integral oil‐gas plume model simulating the Deepwater Horizon oil spill. The study focuses on six uncertain input parameters—two entrainment parameters, the gas to oil ratio, two parameters associated with the droplet‐size distribution, and the flow rate—that impact the model's estimates of the plume's trap and peel heights, and of its various gas fluxes. The ranges of the uncertain inputs were determined by experimental data. Ensemble calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…As indicated by Gonçalves et al [ 5 ], the uncertainties in the oil spill location, the amount of the spilled oil, the flow rate of the oil, the oil droplet size distribution, the ocean current, the subgrid-scale parametrization, the wind drag at the surface, the oil degradation, and other parameters would influence the simulated and predicted fate of the spilled oil. It is necessary to investigate the influence of model uncertainties [ 6 , 14 , 16 , 20 , 21 ]. The start time and spill site are the basic temporal and spatial information for simulating the underwater oil spill, and the wind and current are the necessary input for the underwater oil spill model.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As indicated by Gonçalves et al [ 5 ], the uncertainties in the oil spill location, the amount of the spilled oil, the flow rate of the oil, the oil droplet size distribution, the ocean current, the subgrid-scale parametrization, the wind drag at the surface, the oil degradation, and other parameters would influence the simulated and predicted fate of the spilled oil. It is necessary to investigate the influence of model uncertainties [ 6 , 14 , 16 , 20 , 21 ]. The start time and spill site are the basic temporal and spatial information for simulating the underwater oil spill, and the wind and current are the necessary input for the underwater oil spill model.…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of model uncertainties is required for reliable numerical simulation and prediction [ 16 ]. Elliott and Jones [ 17 ] indicated that the wind was a much more important requirement for simulating an oil slick than the current, buoyancy, and weathering processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In those applications, traditional spectral projection methods [12,15,16] to construct the PC model were successfully implemented. In recent studies, however, the spectral projection technique failed to construct faithfully a PC expansion that represents the forward model [17,55]. This was due to the non-linearity of the forward model and to the internal noise that was present, leading to PC expansion convergence issues.…”
Section: Introductionmentioning
confidence: 99%
“…The BPDN method offers an additional advantage that a smaller number of model runs compared to the spectral projection method is required to determine the PC coefficients as shown in Section 4c. BPDN was recently employed to build a proxy model for an integral oil-gas plume model (Wang et al 2015) and for an ocean model with initial and wind forcing uncertainties (Li et al 2015). In the former, the model output was noisy due to the iterative solver used in the double-plume calculation (Socolofsky et al 2008) and BPDN proved to be successful in filtering the noise and thus building a representative PC model.…”
Section: Introductionmentioning
confidence: 99%